2017
DOI: 10.1007/s10557-016-6708-8
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as an Agent for Cardioprotection in Patients with ST-Elevation Myocardial Infarction and Short Ischaemic Time

Abstract: We were interested in the Review article written by Kloner et al., about of the cardioprotection in patients with acute myocardial infarction. The authors should be congratulated for this excelent review. The authors discuss the recent successes as well as recent disappointments, and describe some of the newer potential therapies in cardioprotection in patients with acute myocardial infarction [1]. However, we would like to point out that there is a recent pharmacological therapy which has been investigated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…19 Recently, its cardioprotective function has gained a great deal of attention. [20][21][22][23] More and more evidence suggests that the cardioprotective functions of melatonin are due to its direct free radical scavenger properties, antioxidant activities and anti-inflammatory effects. In this study, we confirmed the cardioprotective role of melatonin in an animal model of MI, and for the first time we found that melatonin improved cardiac remodeling a Sirt6-dependent antioxidant pathway.…”
Section: Discussionmentioning
confidence: 99%
“…19 Recently, its cardioprotective function has gained a great deal of attention. [20][21][22][23] More and more evidence suggests that the cardioprotective functions of melatonin are due to its direct free radical scavenger properties, antioxidant activities and anti-inflammatory effects. In this study, we confirmed the cardioprotective role of melatonin in an animal model of MI, and for the first time we found that melatonin improved cardiac remodeling a Sirt6-dependent antioxidant pathway.…”
Section: Discussionmentioning
confidence: 99%